Biomimetic strategies of cell membrane vesicles driven by pathogen-host interactions: novel insights into antimicrobial immunotherapy and infection prevention - Xia, Ximin; Fang, Yu; Zhong, Jia; Li, Fanzhu; Jiang, Lai (Frontiers in Immunology, 2025)
Cell membrane vesicles (CMVs), including outer membrane vesicles from bacteria and exosomes from mammalian cells, have attracted growing attention due to their diverse roles in microbial pathogenesis and immune regulation. These vesicles not only facilitate the delivery of toxins and resistance factors during infection but also serve as critical messengers shaping host immune responses. In this review, we explore the bidirectional communication mediated by CMVs within pathogen-host networks, highlighting their influence on infection dynamics, immune evasion, and inflammation resolution. We further examine how these biological insights have inspired novel therapeutic strategies: engineered CMVs-based nanodecoys that block bacterial adhesion or neutralize virulence factors, and CMVs-derived nanoformulations that promote targeted immune activation. Recent advances in vesicle bioengineering have enhanced their targeting precision and immunogenic potential, offering promising solutions against antibiotic-resistant bacteria. Despite the progress, challenges related to production scalability, quality control, and regulatory approval remain significant. Continued interdisciplinary efforts are needed to advance CMVs-based technologies toward clinical application in infectious disease prevention and immune therapy.